METHODOLOGY FOR TEACHING INFORMATION TECHNOLOGY AND PROCESS MODELING ON THE BASIS OF INNOVATIVE METHODS - Rustamov Mirodiljon Muhammadjanovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract:      The rapid advancements in Information Technology (IT) and its integration into various fields have made IT education essential for future professionals. Teaching IT and process modeling requires a robust methodology that combines theoretical knowledge with practical application. This article explores innovative teaching methods that enhance learning outcomes, including project-based learning, gamification, flipped classrooms, and collaborative learning. By implementing these approaches, educators can foster critical thinking, problem-solving skills, and creativity among students. The paper outlines a framework for applying these methods and discusses their impact on student engagement and knowledge retention.